Mobile and ubiquitous systems: computing, networking, and services : 9th International Conference, MobiQuitous 2012, Beijing, China, December 12-14, 2012. Revised Selected Papers - Li, Mo; Jiang, Hongbo; Zheng, Kan (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 9th International ICST Conference on Mobile and Ubiquitous Systems: Computing, Networking, and Services, MobiQuitous 2012, held in Beijing, China, Denmark, in December 2012. The revised full papers presented were carefully reviewed and selected from numerous submissions. They cover a wide range of topics such as localization and tracking, search and discovery, classification and profiling, context awareness and architecture, location and activity recognition. The proceedings also include papers from the best paper session and the industry track, as well as poster and demo papers.